SYMGERBI - Cardoso Telles, Arthur; do Nascimento Filho, Alex Carlos; Carvalho Ferreira, Henrique; Brucy Dias Martins, Hyago; Araujo Medrado, Jean Carlos; Alves de Godoi, Kariny; dos Reis Pereira Fanstone, Pollyana (CIPEEX, 2022)
HEALTH SERVICE WASTE, COMMONLY ASSOCIATED WITH THE TERM HOSPITAL WASTE OR HOSPITAL WASTE, IS THE NAME GIVEN TO WASTE ORIGINATING FROM MEDICAL ACTIONS DEVELOPED IN HEALTH CARE UNITS, IN PREVENTION, DIAGNOSIS, TREATMENT, REHABILITATION AND RELATED RESEARCH ACTIVITIES. WITH HUMANS OR ANIMALS, IN PHARMACIES, IN MEDICO-LEGAL ACTIVITIES, IN TEACHING AND IN ANY OTHER ACTIVITIES THAT INVOLVE INVASIVE PROCEDURES. THIS WORK AIMED AT THE STUDY AND CREATION OF A SOFTWARE WITH THE OBJECTIVE OF PROVIDING A MORE AGILE FORM OF ORDER TO CORRECTLY DISCARD THE GARBAGE, FAVORING COMMUNICATION BETWEEN HOSPITALS AND CLINICS WITH THE RESPONSIBLE COMPANY. THE PROJECT HAS AN OBJECTIVE A SEARCH FOR SIMPLICITY FOR COLLECT, IN VIEW OF THE USE OF METHODS SUCH AS LEAN INCEPTION AND A BETTER UNDERSTANDING OF THE PRODUCT SO THAT USERS HAVE GREATER EASE AND AGILITY, WITHOUT CAUSING A DROP IN PERFORMANCE IN THE PRODUCT OR IN THE DEVELOPMENT. IT IS ALSO EXPECTED THAT THE ENTIRE TOOL DEVELOPMENT PROCESS SEEKS TO BRING A BETTER EXPERIENCE TO THE JOB MARKET. AS IT IS IN ITS INITIAL PHASE, TOOLS WERE USED FOR PLANNING SUCH AS: BPMN, WHERE THERE WAS AN ATTEMPT TO OUTLINE THE BASIC FUNCTIONALITIES OF THE FIRST PROTOTYPE, THE DISCUSSION AND DEFINITION OF FUNCTIONAL AND NON-FUNCTIONAL REQUIREMENTS AND BUSINESS RULES WAS ALSO CARRIED OUT, IN ADDITION TO THE COMPOSITION OF A PERSONA IN ORDER TO BETTER DIRECT THE CREATION OF THE SOFTWARE, THE DESIGN OF THE PAGES, LAYOUT AND COLORS, ALWAYS KEEPING IN MIND THE NEEDS OF THE CLIENT, SEEKING TO FACILITATE UNDERSTANDING AND REDUCE THE EFFORT ON THE PART OF THE CLIENT. AFTER BE NOTICED THE LACK OF INFORMATION ABOUT THIS TYPE OF CONTENT, THE GREAT NEED TO TALK ABOUT PROBLEMS CAUSED BY HOSPITAL WASTE, MAINLY DUE TO THE SARS COV-2 (COVID 19) PANDEMIC, AND WITH RECENT DISCUSSIONS ON THE SUBJECT, THERE WAS A CONCLUSION OF THE DEVELOPMENT OF A SOFTWARE FOR IN ORDER TO PROVIDE A SIMPLER AND MORE AGILE COMMUNICATION BETWEEN HOSPITALS AND COMPANIES SPECIALIZED IN TRANSPORT AND DISPOSAL, WITH THE AIM OF NO LONGER HAVING SCENES OF SOMETHING SO DANGEROUS LEFT ANYWHERE. THE INITIAL IDEA WAS JUST THE CREATION OF A WEBSITE, WHERE THE DISPOSAL COMPANY AND HOSPITALS COMMUNICATED, BUT AS THE CONVERSATIONS PROGRESSED, THE NEED TO NEGOTIATE DISPOSAL WAS REALIZED IN ORDER NOT TO LET THE DISPOSAL OCCUR INCORRECTLY. AFTER SEVERAL DISCUSSIONS, IT WAS CONCLUDED THAT THE BEST WAY TO LINK THE PERSON RESPONSIBLE FOR CREATING THE INFECTIOUS WASTE WITH THE PERSON RESPONSIBLE FOR DESTROYING IT WOULD BE TO CREATE A WEBSITE WHERE HOSPITALS, CLINICS, PET SHOPS COULD REGISTER AND FROM THERE REQUEST THE COLLECTION OF GARBAGE, AND THE CREATION OF A PROGRAM WHERE THE INCINERATOR WOULD RECEIVE THIS REQUEST ALONG WITH THE APPLICANT'S INFORMATION, SUCH AS ADDRESS, TYPE OF WASTE, AND APPROXIMATE QUANTITY.